A clinical case of X-linked adrenoleukodystrophy in a 9-year-old boy - Ya. V. Girsh (Bûlleten' Sibirskoj Mediciny, 2022)
X-linked adrenoleukodystrophy belongs to peroxisomal disorders characterized by combined damage to the nervous system and adrenal glands and often leading to death. This hereditary disease results in mutations in the ABCD1 gene, leading to ineffective β-oxidation of fatty acids following a decrease in the activity of acetyl-CoA synthetase of their long chains. Accumulation of acyl-CoA derivatives of fatty acids takes place, which affect the physicochemical properties of cell membranes.We have described a clinical case of X-linked adrenoleukodystrophy in a 9-year-old boy with the primary manifestation of the disease at the age of 7 years and 10 months in form of enterovirus encephalitis.Early diagnosis, prenatal screening of adrenoleukodystrophy for performing gene-specific therapy, slowing the progression of the disease, and prolonging the life of the patient with the diagnosis of a rare hereditary disease are required.